CARBON FARMING: POTENTIAL FOR MITIGATING CLIMATE CHANGE IN BRAZILIAN AGRICULTURAL SOILS - Vendite, Gabriela Gonçalves; Oliveira, Anna Hoffmann (Editora Impacto Científico, 2025)
One of the greatest contemporary socio-environmental challenges, climate change poses risks to food security and the resilience of tropical agroecosystems. In this context, the set of soil management practices known as carbon farming represents a smart strategy for maximizing carbon sequestration and reducing net greenhouse gas emissions from agricultural activities. This study evaluated the effectiveness of these practices in Brazil through a Systematic Literature Review (SLR), based on the PRISMA protocol. Fifty-six articles published between 2015 and 2025 were analyzed, extracted from the SciELO, Web of Science, Scopus, and Google Scholar databases. The studies were organized into thematic areas, with emphasis on the frequency of publications for: no-till farming and crop rotation (25%), crop-livestock-forest integration (18%), pasture recovery (16%), and agroforestry/silvopastoral systems (14%). The results indicated consistent gains: SPD increased stocks by up to 1.5 Mg C ha⁻¹ year⁻¹; cover crops reduced nitrogen fertilization by up to 30%; water management in irrigated rice mitigated up to 96% of CH₄ emissions; fertigation in sugarcane reduced N₂O by 50%; pasture recovery and silvopastoral systems added up to 1.2 Mg C ha⁻¹ year⁻¹; ILPF increased up to 2.8 Mg C ha⁻¹ year⁻¹; and SAFs/SPS achieved up to 7 Mg C ha⁻¹ year⁻¹. It can be concluded that carbon farming constitutes a portfolio of effective and complementary practices, but its large-scale expansion depends on overcoming technical and economic barriers, in addition to strengthening public policies.DOI: https://doi.org/10.56238/edimpacto2025.085-005